THE ANATOMY OF CAROTENE BIOSYNTHESIS IN BETA VULGARIS L., VAR. RUBRA USING SCAN ELECTRON MICROSCOPE - Dahlia Dahlia (UNEJ e-Proceeding, 2016)
Beta vulgaris L., var. rubra is plant containing much carotene. Carotene and various kind of carotene are biosynthesis at leaf. It is transported with the stem and stored in the certain places. The aim of this study is to observe the anatomy structure of leaf, stem and bulb/root, containing carotene in Beta vulgaris l., var. rubra. The sample was gained from Cangar, Malang which the old was about 2 months. We analyzed it using scan electron microscope.